Public Policies Under Tension: Tourism and Environmental Protection - A Case Study in Patagonia - Lolich, Liliana (2015)
Fil: Lolich, Liliana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina.